2019
DOI: 10.5056/jnm19041
|View full text |Cite
|
Sign up to set email alerts
|

Second Asian Consensus on Irritable Bowel Syndrome

Abstract: Background/Aims There has been major progress in our understanding of the irritable bowel syndrome (IBS), and novel treatment classes have emerged. The Rome IV guidelines were published in 2016 and together with the growing body of Asian data on IBS, we felt it is timely to update the Asian IBS Consensus. Methods Key opinion leaders from Asian countries were organized into 4 teams to review 4 themes: symptoms and epidemiology, pathophysiology, diagnosis and investigations, and lifestyle modifications and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 213 publications
(264 reference statements)
3
94
0
Order By: Relevance
“…Accordingly, increased levels of fecal amino acids could be considered as important disease‐relevant features of IBS‐D, and threonine, tryptophan, and phenylalanine might be potential therapeutic targets for IBS‐D. Serotonin modulating therapies have been already used to control IBS symptoms . Further studies are needed to evaluate the exact relationships between threonine and phenylalanine and IBS‐D and develop novel therapeutic agents modulating these amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, increased levels of fecal amino acids could be considered as important disease‐relevant features of IBS‐D, and threonine, tryptophan, and phenylalanine might be potential therapeutic targets for IBS‐D. Serotonin modulating therapies have been already used to control IBS symptoms . Further studies are needed to evaluate the exact relationships between threonine and phenylalanine and IBS‐D and develop novel therapeutic agents modulating these amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Irritable bowel syndrome is multifactorial in pathogenesis 1–3, 15, 16 . These factors may be broadly classified into (i) peripheral factors 17 (viz., altered gastrointestinal [GI] motility, GI inflammation and permeability alteration, altered luminal microenvironment including gut microbiota dysbiosis and small intestinal bacterial overgrowth [SIBO], host–microbe interaction, bile acid recirculation defect, pathogenic infection, dietary factors, and neurohumoral dysregulation including altered serotonergic transmission and visceral hypersensitivity) and (ii) central factors (psychological stress, cognitive dysfunction, abnormal emotional arousal system response, and sleep dysfunction).…”
Section: Factors Implicated In the Pathogenesis Of Irritable Bowel Symentioning
confidence: 99%
“…Whereas patients with constipation‐predominant IBS (IBS‐C) have slow gut, particularly colonic, transit, diarrhea‐predominant IBS (IBS‐D) patients have faster motility 1, 5, 19 . Multiple studies showed that Bristol stool form is determined by colonic motility; slower colon transit is associated with harder stools 20, 21 .…”
Section: Altered Gastrointestinal Motility In Irritable Bowel Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…1 IBS is a chronic disorder that may lead to impaired personal and social interactions of affected individuals. 2,3 However, the pathophysiology of IBS is still unclear. Various factors including visceral hypersensitivity, abnormal gut motility, immune activation, disorder of the brain-gut axis, impaired intestinal barrier function, and alteration of gut microbiota, have been suggested as main causes of IBS in previous literatures.…”
Section: Introductionmentioning
confidence: 99%